Towards Inclusive Higher Education: Curriculum Innovation through Optional Subject Integration for Students with Special Needs - Arju, Sayma; Ho, Jana Chi-san (European Scientific Journal, ESJ, 2026)
Students with special needs (SSNs) have been slowly but significantly increasing in higher educational institutions (HEIs) of Bangladesh in recent years. Though their inclusion is generally welcomed by university authorities, a significant gap remains in both faculty capacity and curriculum inclusivity. SSNs often receive few accommodations from HEIs, such as assistance from a reader during examinations, extended time (usually 30 minutes), ramps for physical access, or limited library resources, such as braille materials or text-to-speech software, which are far from sufficient. The curriculum followed in most universities is designed primarily for students without disabilities, which puts SSNs at a disadvantage, as they might struggle to compete on equal terms and are unable to demonstrate their true potential under standard teaching and assessment methods. To address this gap, SSNs should be offered optional subjects aligned with their interests and strengths. Such alternatives could improve their motivation and academic performance. This case study-based research explored how three students with special needs improved their academic grades when they were allowed to substitute two of their regular curriculum courses, which they found difficult due to their specific challenges, with two supportive and interest-based courses. Additionally, 30 SSNs were interviewed to determine which electives they would like to be included in the curriculum. Findings suggest that a dedicated pool of electives, designed and offered exclusively for SSNs with appropriate instructional and infrastructural support, can have a significant positive impact. The present study proposed a need-based curriculum design (NBCD) model to foster genuine inclusiveness within HEIs.